Increased MUC1 plus a larger quantity and complex size for MUC5AC in the peripheral airway lumen of long-term tobacco smokers. Issue 10 (21st May 2020) - Padra, Médea; Andersson, Anders; Levänen, Bettina; Premaratne, Pushpa; Asgeirsdottir, Helga; Tengvall, Sara; Christenson, Karin; Stockfelt, Marit; Bozinovski, Steven; Yoshihara, Shigemi; Lantz, Ann-Sofie; Palmberg, Lena; et al.
Abstract: There is little information on mucins versus potential regulatory factors in the peripheral airway lumen of long-term smokers with (LTS+) and without (LTS−) chronic obstructive pulmonary disease (COPD). We explored these matters in bronchoalveolar lavage (BAL) samples from two study materials, both including LTS+ and LTS− with a very similar historic exposure to tobacco smoke, and healthy non-smokers (HNSs; n =4–20/group). Utilizing slot blot and immunodetection of processed (filtered and centrifuged), as well as unprocessed BAL samples from one of the materials, we compared the quantity and fraction of large complexes of mucins. All LTS displayed an enhanced (median) level of MUC5AC compared with HNS. LTS− displayed a higher level of large MUC5AC complexes than HNS while LTS+ displayed a similar trend. In all LTS, total MUC5AC correlated with blood leukocytes, BAL neutrophil elastase and net gelatinase activity. Large mucin complexes accounted for most MUC5B, without clear group differences. In all LTS, total MUC5B correlated with total MUC5AC and local bacteria. In the same groups, large MUC5B complexes correlated with serum cotinine. MUC1 was increased and correlated with BAL leukocytes in all LTS whereas MUC2 was very low and without clear group differences. Thus, the main part of MUC5AC and MUC5B is present as large complexes in the peripheral airway lumen and historic as well as current exposure to tobacco smoke emerge as potential regulatory factors, regardless of COPD per se . Bacteria, leukocytes and proteinases also constitute potential regulatory factors, of interest for future therapeutic strategies.